Study of dug well water quality in Labuan Bajo, Indonesia - Daniel Wolo; Anna S. Rahmawati; Melania Priska; Insar Damopolii (Jurnal Biologi Tropis, 2020)
The dug well water quality in community settlements needs assessment to ensure its quality. The water has to meet the required physical, chemical, and bacteriological standards. This initial research aimed to determine the dug well water quality in Kampung Ujung, Komodo District, Labuan Bajo City, WestManggarai Regency in September 2019. The research method was used survey and laboratory. The two dug well was taken used a purposive sampling technique. The test parameters include temperature, turbidity, pH, smell, Total Suspended Solid (TSS), sulfate, Total Dissolved Solid (TDS), nitrate, nitrite, Total Hardness, Dissolved Oxygen (DO), nitrogen ammonia, total coliforms, and Escherichia coli. The analysis physically, chemically, and biologically of two dug well water samples were had done examined. The result showed that the parameters of TDS, nitrate, nitrite, E. coli, and DO exceed the Class I Water Quality Standard. The research concluded that the quality of both dug well water in the Kampung Ujung Labuan Bajo area was not suitable for use as material raw drinking water. Furthermore, the government should provide other water sources such as the addition of storage tanks for raw water, so that people do not entirely depend on dug well water.